ANALISIS PENGGUNAAN TERTINGGI DAN TERBAIK TANAH KOSONG MILIK PT.PERTAMINA (PERSERO) (Studi pada Tanah di Jl. Raya Pasar Minggu Km.16, Jakarta Selatan) - , Patricia Endang Bramiyastie, S.IP.; , Dr. Wakhid Slamet Ciptono, M.B.A., M.P.M. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
The highest and best use research for the vacant land which owned by PT Pertamina (Persero) at Jalan Raya Pasar Minggu KM.16, South Jakarta, was conducted through analysis process of property productivity in law aspect, regulation and also aspect of physical and location. Furthermore, it was also conducted with supply and demand market analysis, and financial feasibility analysis for each proposed usage. The data to be analyzed consists of primary data and secondary data. Primary data includes data revenues, rents and expenditures that proposed as an alternative obtained by a structured interview, while the physical data including the size, footprint shape, utilities and others obtained through interview and observation, while secondary data was obtained from the Colliers International Indonesia, the Ministry of Finance, Bank Indonesia. From all of the analysis there were two proposals obtained, appropriate land use and allow the use of office buildings and shopping centers. Based on indicators of financial viability with the Net Present Value (NPV), Internal Rate of Return (IRR), Pay Back Period (PBP), the use of shopping centers indicated better than the office building so it can be concluded that the alternative use of the shopping center is the most optimal.